Ionization, negative ion formation, elastic scattering and spin exchange in H + H collisions at low- to intermediate-energies. (3rd April 2017) - Ovchinnikov, S Yu; Kamyshkov, Y; Zaman, T; Schultz, D R
Abstract: A new, two-electron transition mechanism is identified that provides the dominant pathway for negative ion formation in 1–20 keV H + H collisions revealed by use of the so-called 'hidden crossings' theoretical framework. This transition is made via a branch point between sheets of the complex, quasi-molecular, electronic potential energy surface for singlet states. Good agreement between measurements and the theoretically predicted cross sections is obtained. This mechanism also provides a pathway for ionization in this energy range adding to that previously identified (Bent et al 1998 J. Chem. Phys. 108 1459) involving hidden crossings among the triplet quasi-molecular states, improving the agreement of the resulting theoretical predictions with measurements between 2 and 20 keV. Also improving agreement with measurements is the addition of the effect of Rosenthal oscillations that are superposed upon the ionization and negative ion formation cross sections. We note that in addition to fundamental new insight provided by these calculations, the resulting data support modeling of hydrogen gases and plasmas such as in astrophysical environments and terrestrial laboratory experiments. Further supporting such needs for H + H collision data, we have also created a new and more comprehensive data set that significantly updates previous work (Krstic and Schultz 1999 J. Phys. B: At. Mol. Opt. Phys. 32 3485 and references therein) of elastic scattering and spin exchange integral and differential cross sections.